KONVERGENSI AKTOR KELEMBAGAAN DALAM PENANGANAN STUNTING DI KABUPATEN SUMEDANG - Moch. Farhan Hermawan; Eka Purna Yudha; Kuswarini Kusno; Adi Nugraha (Universitas Galuh, 2023)
Stunting reduction programs are important to be carried out with a multi-sectoral approach through the synchronization of national, local, and community programs at the central and regional levels. The convergence of stunting prevention can fill the empty spaces of interventions that have been carried out. The purpose of this study is that researchers want to know how the level of influence and dependence between institutional actors in stunting prevention efforts, then how is the relationship between institutional actors' goals in stunting prevention efforts. Stakeholder analysis method using Matrix of Alliance Conflict: Tactic, Operation, and Responses (MACTOR). The results showed that the actor with the highest influence was the Department of Public Works, while the actor with the highest dependence was the Department of Health. Actors who have the same goals will have the potential to collaborate, while actors who have different goals will generate potential conflicts. Actors who responded positively to the goals and were able to collaborate were Bappeda, the Health Office, and the Family Planning Office. Meanwhile, those who gave a negative response related to the goals that had been set were college actors.